Carcinosarcoma of the Bladder: A Case Report and Review of the Literature - Doğan Atılgan; Yusuf Gençten (Case Reports in Urology)
Carcinosarcoma of the urinary bladder is a rare neoplasm that is composed of malignant epithelial and mesenchymal components. In these tumors, histogenesis and biological behaviour remain controversial. Approximately 70 cases have been reported in the literature, usually as case reports or a small series. A series of 221 cases using the Surveillance, Epidemiology and End Results (SEER) Program database has been reported recently. Optimal treatment is uncertain. Herein, we report a case of sarcomatoid carcinoma of urinary bladder of a farmer aged 84 years old with a year history of hematuria and dysuria. A transurethral resection of the tumor (TUR-T) revealed a carcinosarcoma. The patient underwent radical cystectomy, and there is no tumor recurrence for 15 months after treatments.